Considerably improved water and oil washability of highly conductive stretchable fibers by chemical functionalization with fluorinated silane. Issue 39 (30th September 2019) - Lee, Yoojin; Bae, Seonghyun; Hwang, Byungil; Schroeder, Marc; Lee, Yongwoo; Baik, Seunghyun
Abstract : The chemical functionalization with fluorinated silane provides considerably improved water and oil washability of highly conductive stretchable nanocomposite fibers. Abstract : There have been significant improvements in conductive stretchable fibers and fabrics over the last few decades. However, the durability against washing ( i.e., washability) still remains as a challenging issue hindering practical applications for wearable electronics. In this study, the water and oil washability of conductive stretchable nanocomposite fibers were significantly improved by the covalent functionalization with trichloro(1 H, 1 H, 2 H, 2 H -perfluorooctyl)silane (FOTS). The highly conductive (∼14 600 S cm −1 ) stretchable AgPU fibers were synthesized by the wet spinning technology using flower-shaped silver nanoparticles and polyurethane (PU). The PU surface of the fiber was firstly treated by Ar plasma to induce reactive hydroxyl groups for the covalent binding with the silane molecules. The vapor-phase FOTS deposition was then carried out to synthesize FOTS-AgPU fibers. Both hydrophobicity and oleophobicity significantly improved after the functionalization. There was negligible change in the electrical conductivity, mechanical strength, and rupture strain of the FOTS-AgPU fiber after 8 thorough detergent water washing cycles, demonstrating almost perfect water washability with laundry detergent. The thermal conductivity slightly decreased by 10% since it was more challenging to maintain the phononic thermal transport than the electrical transport. The oil washability was also improved although perfect passivation could not be achieved. The FOTS layer could also be directly functionalized on the AgPU fabric, instead of the AgPU fibers, demonstrating the possibility of facile up-scale post-functionalization. The conductive stretchable fibers and fabric with improved water and oil washability may find immediate applications for wearable electronics.